Platelet Aggregation: Newly Quantified Using NonEmpirical Parameters - Nichols, Alan R; Bosmann, H Bruce (Thrombosis and Haemostasis, 1979)
New methodology for a quantitative description of adenosine diphosphate (ADP)- induced human blood platelet aggregation in vitro is presented. The method uses electronic particle size analysis to determine the relative amounts of and distribution of sizes among platelets and aggregates after rapid termination of the events of ADP-induced aggregation by glutaraldehyde. Glutaraldehyde is found to preserve the state of platelets and aggregates in suspension unchanged for up to 48 h.Descriptions of platelet aggregate sizes and amounts at many points during reversible and irreversible aggregation at 37° C as they occur in the Platelet Aggregometer are discussed. A new model of reversible platelet aggregation emerges revealing previously unrecognized details of both the aggregation and disaggregation phases of the phenomenon and establishing that disaggregation is not simply the ‘mirror image’ of aggregation. Furthermore, the reactive proportions of the platelet population under conditions of both ADP- induced reversible and irreversible aggregation are very similar, strongly suggesting that other factors are responsible for the observed large differences in aggregation rates and resulting aggregate sizes. Correlations between Platelet Aggregometer parameters and the aggregate size distributions are considered, and the first report of a correlation between the average platelet composition of particles in the aggregated suspensions and the absorbance change as recorded by the Aggregometer is made. Also, the relationship between particle concentration of a suspension of platelets and aggregates and the suspension absorbance is non-linear. Heretofore unrecognized limitations of the Platelet Aggregometer are revealed. Importantly, absorbance as measured by the Aggregometer does not uniquely represent the magnitude of formed aggregates.